Spider in the Well - Hannigan, Jess (New York, NY : Katherine Tegen Books, an imprint of HarperCollinsPublishers, 2024)
"Breaking News: Wishing Well Broken! The townspeople of Bad Göodsburg are up in arms. With their beloved well busted, none of their important, generous, kindhearted wishes are coming true! Time to send that good-for-nothing Newsboy to investigate..."--.
new kids book 2024 spring.
Ages 4-8
Grades K-1
Keywords: Newspaper vendors -- Juvenile fiction; Wishing wells -- Juvenile fiction; Spiders -- Juvenile fiction; Newspaper vendors -- Fiction; Wishing wells -- Fiction; Spiders -- Fiction; Picture books; Picture books